On Local Linear Regression Estimation in Sampling Surveys - Kikechi, Conlet B.; Simwa, Richard O.; Pokhariyal, Ganesh P. (Pushpa Publishing House, 2017)
A model based survey is employed to estimate the unknown values of the survey variable, using the local linear regression approach. In particular, a local linear regression estimator in model based surveys is studied. Variance comparisons are made between the derived estimator and the Nadaraya-Watson regression estimator which show that the two estimators are asymptotically equivalently efficient.
Keywords: Survey sampling; Auxiliary information; Local linear regression estimator; Model based surveys; Nonparametric regression; Asymptotic relative efficiency